Proceedings in the matter of a postponement of the execution of a sentence - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This article focuses around the issue of sentence deferment proceedings. It concerns not only the court of first instance stage but the appeal procedure as well. It is important as the Criminal Enforcement Code regulates differently the rules of enforcement proceedings. Further actions leading to the release of decree regarding sentence deferment have been described in detail, as well as the rules of the complaint proceedings.
Keywords: odroczenie wykonania kary; obrońca; pismo procesowe; dekret; procedura odwoławcza